2017
DOI: 10.1039/c7ra05544g
|View full text |Cite
|
Sign up to set email alerts
|

Subphthalocyanine-based porous organic polymers

Abstract: The synthesis and photophysical properties of two subphthalocyanine-based porous organic polymers (SubPc-POPs) are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Axial substitution of the axial chlorine atom with phenols is commonly carried out by refluxing the starting SubPc-Cl with the corresponding alcohol in a high-boiling point aromatic solvent such as toluene, 46–48,50,53–56,58,70,73,76,91–117 1 : 1 toluene/THF mixture, 118 chlorobenzene, 17,119 dichlorobenzene (DCB) 29,30 and o -xylene. 120 Interestingly, reaction of SubPc-Cl, SubPc-Br and mesylated SubPcs with phenols in DMF was found to afford the corresponding formate derivative in addition to the target phenoxy conjugate and the hydrolyzed SubPc-OH product ( vide infra ). 121 Axial substitution with phenols can be performed by a one-pot two-step procedure without purification of the chlorinated precursor, by adding the aryl alcohol and the solvent directly to the crude cyclotrimerization product.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 2 more Smart Citations
“…Axial substitution of the axial chlorine atom with phenols is commonly carried out by refluxing the starting SubPc-Cl with the corresponding alcohol in a high-boiling point aromatic solvent such as toluene, 46–48,50,53–56,58,70,73,76,91–117 1 : 1 toluene/THF mixture, 118 chlorobenzene, 17,119 dichlorobenzene (DCB) 29,30 and o -xylene. 120 Interestingly, reaction of SubPc-Cl, SubPc-Br and mesylated SubPcs with phenols in DMF was found to afford the corresponding formate derivative in addition to the target phenoxy conjugate and the hydrolyzed SubPc-OH product ( vide infra ). 121 Axial substitution with phenols can be performed by a one-pot two-step procedure without purification of the chlorinated precursor, by adding the aryl alcohol and the solvent directly to the crude cyclotrimerization product.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…Deprotection of silyl ether groups in the presence of CsF in acetone and subsequent reaction of the hydroxy-substituted SubPc with 1,4-benzene diboronic acid have also been reported. 120…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of F-SubPCs, as shown in Scheme 2, was accomplished by adapting previous literature procedures [23]. In brief, the phthalonitrile precursors 1-3 were prepared by an SNAr reaction of the fluoroalkyl thiols and halogenated phthalonitriles.…”
Section: Synthesis Of F-subpcsmentioning
confidence: 99%
“…[12] This work clarified that BsubPc is an aromatic macrocycle with resonance, as isoindoline and imide bonds around the boron complex are equally distributed in the solid state. Interestingly, it was later found that BsubPc-based linear [13][14][15] and porous [16,17] polymeric materials can be formed. Years later, the lack of systematic BsubPc structural analysis prompted Virdo et al to reconfirm the solid-state structure and examine its possible dependence on several variables.…”
Section: Introductionmentioning
confidence: 99%